Correlation between Quantitative 13C-Urea Breath Test and Helicobacter pylori Treatment Success in a Population-Based Cohort. (13th November 2018) - Boltin, Doron; Levi, Zohar; Perets, Tsachi Tsadok; Schmilovitz-Weiss, Hemda; Gingold-Belfer, Rachel; Dickman, Ram; Dotan, Iris
Abstract : Background . There are continual efforts to identify factors which influence the success of first-line therapy for Helicobacter pylori ( H. pylori ) infection. The 13 C-urea breath test result (C13-UBT) utilizes H. pylori urease activity and is a highly accurate diagnostic assay. We aimed to determine whether the magnitude of C13-UBT result is related to treatment success. Methods . Adult patients who underwent a first-time 13 C-urea breath test between January 2010 and January 2016 were included. In order to isolate a naïve test-and-treat population who were unlikely to have undergone an initial endoscopy-based H. pylori test, we excluded patients > 45 years and those with a previous C13-UBT. Data were extracted from the Clalit Health Services laboratory database. Results . A total of 94, 590 subjects (36.1% male, age 28.5 ± 6.0 years) who underwent a first-time C13-UBT during the study period were included. C13-UBT was positive in 48, 509 (51.3%) subjects. A confirmatory posttreatment C13-UBT was performed in 18, 375 (37.8%), and eradication was successful in 12, 018 (65.4%). The mean C13-UBT recording was 20.6 ± 16.2 DOB in subjects with successful eradication and 19.5 ± 13.1 DOB in subjects with treatment failure (OR, 1.01; 95% CI 1.00-1.01, p < 0.01 ). Among patients in the upper quintile of C13-UBT measurement, eradication was achieved in 67.6%, compared to 62.6% in the lower quintile (OR, 1.22; 95% CI 1.11-1.35, p < 0.01 ). Subjects in the top 1 percentile (C13-UBT ≥ 70 DOB) achieved eradication in 75.0%, compared to 65.3% among subjects with C13-UBT < 70 DOB (OR, 1.59; 95% CI 1.05-2.41, p < 0.01 ). Conclusions . The superiority in H. pylori eradication observed in subjects with a higher C13-UBT DOB is small but significant. Further studies should examine the physiological and microbiological basis for this finding.